2021
DOI: 10.3390/v13010114
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Efficacy, Potential Cardiotoxicity and Monkey Pharmacokinetics of GLP-26 as a Potent Hepatitis B Virus Capsid Assembly Modulator

Abstract: While treatment options are available for hepatitis B virus (HBV), there is currently no cure. Anti-HBV nucleoside analogs and interferon-alpha 2b rarely clear HBV covalently closed circular DNA (cccDNA), requiring lifelong treatment. Recently, we identified GLP-26, a glyoxamide derivative which modulates HBV capsid assembly. The impact of GLP-26 on viral replication and integrated DNA was assessed in an HBV nude mouse model bearing HBV transfected AD38 xenografts. At day 45 post-infection, GLP-26 reduced HBV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…This CAM molecule induces the formation of tight, normal nucleocapsid structures [ 76 ]. In vitro (HepAD38 cells and primary human hepatocytes (PHH)) as well as in vivo (mice models for HBV infection) studies demonstrated that GLP26 exhibits potent antiviral activity against HBV (EC 50 in the low nanomolar range) [ 76 , 77 ]. Moreover, GLP-26 alters cccDNA levels in cell culture models whereas a decrease in both HBeAg and HBsAg levels was observed both in vitro and in vivo.…”
Section: Cam Molecules In Preclinical and Clinical Developmentmentioning
confidence: 99%
“…This CAM molecule induces the formation of tight, normal nucleocapsid structures [ 76 ]. In vitro (HepAD38 cells and primary human hepatocytes (PHH)) as well as in vivo (mice models for HBV infection) studies demonstrated that GLP26 exhibits potent antiviral activity against HBV (EC 50 in the low nanomolar range) [ 76 , 77 ]. Moreover, GLP-26 alters cccDNA levels in cell culture models whereas a decrease in both HBeAg and HBsAg levels was observed both in vitro and in vivo.…”
Section: Cam Molecules In Preclinical and Clinical Developmentmentioning
confidence: 99%
“…Deployment of capsid inhibitors is also expected to slow down the emergence of virus mutants and permit the development of host immune responses that may clear virus replication completely, especially if combined with other modalities. Recent work has shown that such inhibitors are active in vivo with low toxicity and that some act synergistically with nucleoside analogs in a preclinical animal model [ 18 ]. Capsid inhibitors have also shown a modest decrease in the levels of HBV DNA in chronically infected patients [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, new mechanisms inducing and regulating of type IFNs responses has attracted considerable attention [18][19][20] . Recently, hnRNPA2B1 has been viewed as an attracting regulatory protein of IFNs responses for viral infection 12,16 . hnRNPA2/B1, an RNA-binding protein as a member of the hnRNPs family, which plays an important roles in RNA biology and various disease 10,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we assess the function of PAC5 on other viruses, such as pseudotyped SARS-CoV-2 and VSV-G infections. At present, pseudovirus (PsV) has become an ideal tool to analyze cell entry of SARS-CoV-2 without safety concerns and possess the morphological characteristics of replication-competent SARS-CoV-2, with the S protein on the envelope membrane 16 . Here, we first utilized SARS-CoV-2 PsV to perform a series of transduction assays.…”
Section: Pac5 Inhibited Sars-cov-2 and Vsvmentioning
confidence: 99%